El divorcio y sus consecuencias jurídicas, sociales y económicas en los miembros del núcleo familiar en la ciudad de Guaranda en el año 2022. - Valle Gaibor, Omaira Denisse (2024)
Divorce is in itself a way of ending a marriage, which seriously affects the family group, even more so when this breakup is due to acts of violence against women or members of the family nucleus, a context that, unfortunately, became a social phenomenon that affects all Ecuadorian families and, throughout the research territory, Guarandeña families, without any distinction, and even more so, it is reflected more clearly in rural areas and those with low economic status. Therefore, a study begins in the city of Guaranda on the effects of divorce. In such a way that it serves as a prevention for singles to avoid being part of the divorced statistics. That is why the main objective was to analyze the effects of divorce on the family nucleus. With a mixed approach methodology, the starting point is an analysis of the scientific literature on the variables. Using inhabitants over 18 years of age as the population and with intentional sampling by quota, the study unit was analyzed to determine conclusions aligned with the proposed objectives. Therefore, a schedule of activities was proposed for the fulfillment of each of the activities required to fulfill the proposed hypothesis. The expected results, through this research, determined what happens to the members of the family nucleus, during and after a divorce. Keywords: Divorce, marriages, effects, prevention, family nucleus.